TRANSMISSION OF EMBEDDED SKILLS IN MINANGKABAU SOCIETY: AN ANALYSIS OF BEST PRACTICEOF MINANGKABAU MIGRANTS - Mukhneri Mukhtar (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The ethnographic study describes the transmission process of embedded skills within the culture of Minangkabau migrants to explore the cultural domains, taxonomy, components and themes. The study was conducted through three stages, that is, grand tour observation, mini tour observation, and participant observation, involving a number of key informants from the five municipalities of the DKI Jakarta Province, all of whom were working as traders. The focus of observation was on cultural events and the informants’ interactive behaviors. The findings show that transmission of embedded skills occur in the family, clan, and the nagari, and though collaborative work particularly among economically powerful migrants. This indicates (1) the importance of the family, clan, and nagari, in the transmission of embedded skils; (2) the importance of legitimate, rewarded, and expert power for the establishment of leadership, which is taught by the uncle and father in the established migrant group; (3) the importance of consent from the family and clan in determining the migrants’ success; (4) the importance of partnership, internship and organizational system in the transmission of embedded skills; and (5) the importance of parental and entrepreneurial patterns in cultural internalization.